2019
DOI: 10.1111/bju.14649
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular characterisation of the bilateral pelvic nerve crush injury rat model for neurogenic detrusor underactivity

Abstract: Objectives To create a rat model for neurogenic detrusor underactivity (DU) by bilateral pelvic nerve crush injury (BPNI) and to study temporal changes in detrusor contractility and morphology. Materials and Methods Male Sprague‐Dawley rats were subjected to BPNI or sham surgery and evaluated at 1, 3 and 9 weeks after surgery. Bladder function was determined in vivo by awake cystometry, micturition pattern analysis, and 24‐h urine collection. Bladders were harvested for in vitro pharmacological investigation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
(73 reference statements)
4
19
0
Order By: Relevance
“…Such hypersensitivity has been earlier demonstrated in ewes after their first spontaneous delivery 21 . This phenomenon has also been described in the bladder after partial denervation of the detrusor muscle 22 …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Such hypersensitivity has been earlier demonstrated in ewes after their first spontaneous delivery 21 . This phenomenon has also been described in the bladder after partial denervation of the detrusor muscle 22 …”
Section: Discussionsupporting
confidence: 55%
“…21 This phenomenon has also been described in the bladder after partial denervation of the detrusor muscle. 22 To our knowledge, muscarinic receptor 2 (M2) upregulation following trauma has not been previously described in vaginal tissue ( Figure 5). This observation may contribute to the hypersensitivity described above.…”
Section: Discussionmentioning
confidence: 83%
“…In another detrusor underactivity animal model of bilateral pelvic nerve crush injury 58 , 59 , the surgical procedure was different from ours. We used the posterior approach, but they used the transperitoneal approach.…”
Section: Discussionmentioning
confidence: 76%
“…Noritoshi Sekido et al reported an animal model of underactive bladder using lumbar canal stenosis (LCS) 57 . Karel Dewulf et al represented the functional and molecular characteristics of a detrusor underactivity rat model using bilateral pelvic nerve crush injury 58 . However, what is the difference between us and what’s new about us: in Zheng’s model, rats exhibited not only detrusor underactivity but also severe lower limb paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…The hypogastric and pelvic nerves travel through the MPG before reaching target tissues, such as the bladder and urethra 9 . There are several reports about the involvement of these nerves in lower urinary tract function 10‐12 …”
Section: Introductionmentioning
confidence: 99%